PENERAPAN MODEL QUANTUM LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP KELAS VIII - Fauziyyah, Alfi; Inayah, Sarah (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2021)
In learning mathematics, students often have difficulties, many concepts are understood incorrectly, the use of logic and formulas in solving problems is an obstacle for students so that students still consider mathematics as a difficult science. On the basis of the importance of mathematical comprehension ability to be possessed by students in mathematics learning, a quantum learning model is chosen. This study aims to examine the improvement of mathematical comprehension ability of students who get learning with a quantum learning model and students who get ordinary learning; to examine how students behave after learning with the quantum learning model. This type of research is a quasi-experiment with a nonequivalent control group design. The population of this study is all students of class VIII, one of the private junior high schools in Cianjur by choosing two classes as research subjects through the purposive sampling method, namely class VIII D as an experimental class and class VIII E as a control class. The research data was obtained through the results of providing mathematical comprehension ability tests (pretest and posttest). Data analysis improved mathematical understanding using the T-test (independent sample-test) because the data was normally distributed. Based on the results of the study, it can be concluded that the improvement of mathematical comprehension ability of students who get learning using the quantum learning model is better than students who get ordinary learning